EFFECT OF MOLASSES AND CORN AS SILAGE ADDITIVES ON CELL WALL FRACTIONS OF MOTT GRASS SILAGE WITH DIFFERENT FERMENTATION PERIODS - Bilal; M. Q (Journal of Animal and Plant Sciences, 2008)
The aim of the present study was to determine the impact of silage additives on fiber fractions of mott grass silage at varying fermentation periods. For this purpose, mott grass was cut at two stages of maturity (45 and 60 days) from the field of Livestock Experiment Station, University of Agriculture Faisalabad. The cane molasses and crushed corn was used @ 0, 1, 3 and 5 % of the fodder (dry matter) along with three fermentation periods (30, 35 and 40 days). Study results indicated that there was a significant decrease (P <0.05) in neutral detergent fiber (NDF), acid detergent fiber (ADF) and cellulose contents due to additives and fermentation periods. However, an increasing trend in cell wall contents was observed where no additive was added. On over all basis, NDF, ADF and cellulose contents decreased from 72.69-71.47; 43.06-43.70 and 39.86-39.23%, respectively due to increase in additive level from 0-5% but the decrease in NDF and ADF contents was 72.28-71.59 and 42.57-41.97% due to fermentation period. The effect of fermentation period on cellulose contents was non-significant. The addition of molasses @ 3% was found optimum to reduce cell wall fractions at 35days fermentation period.
Keywords: Cell wall fractions; Corn; Fermentation periods; Mott grass; Molasses; Silage.